Pengaruh Kualitas Produk Terhadap Keputusan Pembelian Sepeda Motor Honda Beat Pada CV. LION di Ternate - Brayen Panget; Tinneke M. Tumbel; Lucky D. S. Tamengkel (Universitas Sam Ratulangi, 2018)
In line with his rapid development of science and technology which experienced an increase and change over time underwent logical consequences for the business world by shifting his values to the demands of human needs and desires. This phenomenon brings implication to every company in maintaining the continuity of its operational activities, where the products / services produced are expected to be well received by consumers. Product quality is important in the successful marketing of products / services. Purchase decision is determined by many factors such as product quality that is the researcher's attention with the assumption that if the quality of product is good then it will make the consumer interested so that make the consumer satisfied. This study aims to find out how far the quality of the product to the purchase decision Honda motor beat on CV. LION by taking 86 respondents. the method of analysis used in this research is quantitative method with approach correlation and simple regression, using questionnaires and observations as a technique in obtaining data. In the calculations in this study, researchers use SPSS software version 21. This can indicate whether there is a correlation between the two variables and how much influence the quality of the product to the purchase decision. The result of this research shows that product quality has negative effect on purchasing decision because negative regression coefficient value is 21,608 and every 1% increase of service quality (X), then purchasing decision (Y) will increase by 0,479.Keywords: Product Quality and Purchase Decision